Integrating Islamic Values and Local Wisdom in Designing English Textbook For Islamic Higher Education - Wisran, Wisran; Hartina, St.; Furwana, Dewi (Elsya : Journal of English Language Studies, 2025)
The integration of Islamic values and local wisdom in English language education remains underexplored, particularly in the context of Islamic higher education. Many existing textbooks lack contextual relevance, leaving a gap in materials that can support both linguistic competence and cultural identity. This study seeks to address this gap by developing an English textbook specifically for students of the Islamic Family Law Study Program, incorporating both Islamic values and the local wisdom of Tana Luwu. Using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) Research and Development (R&D) model, the study engaged 50 undergraduate students and three expert validators. The findings suggest a meaningful improvement in students’ English proficiency, as indicated by pre-test and post-test results, which showed a positive learning impact. The validation process also yielded encouraging results, with expert assessments averaging 3.6/4 for content and language, and 3.4/4 for design, suggesting the textbook's strong potential with minor refinements. Student perception surveys further reinforced its effectiveness, with 91% finding the textbook useful, 88% recognizing its cultural and religious relevance, and 80% highlighting its engaging and interactive features. Qualitative feedback highlights greater motivation and a stronger connection to English and Islamic legal principles. This study contributes to culturally responsive pedagogy by providing an empirical, data-driven framework for integrating religious and local cultural values into English language education. Its broader implication lies in offering a scalable model for similar curriculum developments in other disciplines, reinforcing education's role in preserving cultural identity while enhancing linguistic competencies in Islamic higher education.